2016
DOI: 10.1007/s11356-016-7770-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient changes and biodynamics of Eisenia fetida during vermicomposting of water lettuce (Pistia sp.) biomass: a noxious weed of aquatic system

Abstract: This paper reports the results of vermicomposting of water lettuce biomass (WL) spiked with cow dung at ratios of 20, 40, 60, and 80 % employing Eisenia fetida. A total of four treatments were established and changes in chemical properties of mixtures were observed. Vermicomposting caused a decrease in pH, TOC, volatile solids, and C/N ratio by 1.01-1.08-fold, 0.85-0.92-fold, 0.94-0.96-fold, 0.56-0.70-fold, respectively, but increase in EC, N,P, K,Ca, Zn,Fe, and Cu, by 1.19-1.42-fold, 1.33-1.68-fold, 1.38-1.69… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 35 publications
5
16
1
Order By: Relevance
“…The extremely low pH in the case of SCG and the high ammonia content in the case of CS were two determining factors in this study. This is in concordance with Suthar et al [37], who asseverated that a low feeding rate and non-acclimatized environment for newly inoculated worms could have affected the survival of earthworms in waste mixtures. In summary, the mortality trend was T9 > T5 > T4 > T8 > T3 > T2 = T1 > T6 > T7 for this study.…”
Section: Biological Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The extremely low pH in the case of SCG and the high ammonia content in the case of CS were two determining factors in this study. This is in concordance with Suthar et al [37], who asseverated that a low feeding rate and non-acclimatized environment for newly inoculated worms could have affected the survival of earthworms in waste mixtures. In summary, the mortality trend was T9 > T5 > T4 > T8 > T3 > T2 = T1 > T6 > T7 for this study.…”
Section: Biological Resultssupporting
confidence: 91%
“…These results show that mixtures composed of 100% by-product give poor results, similar to recent studies, such as Usmani et al [35], who reported that poor biomass growth of earthworms was observed in the treatment comprised solely of coal fly ash, without manure, and Gong et al [36] where better results were obtained when garden wastes were mixed with cattle manure and/or spent mushroom substrate than in solitary. Similar conclusions were obtained during vermicomposting of water lettuce by Suthar et al [37]. GR (mg weight gained/worm/day) has historically been considered a good comparative index to compare the growth of earthworms.…”
Section: Biological Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Annually, a hundred thousand cubic meters of mixed fresh weed biomass are removed from the Dal Lake by de-weeding harvesters [3]. Aquatic weeds (Nelumbo nucifera, Azolla, Salviniacuculata) produce a number of important secondary metabolites like alkaloids, flavonoids, steroids, triterpenoids, glycosides, and polyphenols [4] and are rich in lipids, carbohydrates, proteins, and minerals [5,6]. Earthworms kept in media Nelumbo leaves for 30 days showed increased body weight and produced relatively more cocoons [7].…”
Section: Introductionmentioning
confidence: 99%
“…Azolla a free floating aquatic weed 17 that lives in association with a blue-green alga, Anabaena azollae (that fixes atmospheric nitrogen) was used as a nitrogen supplement and source of nutrients. The weed biomass rich in fibres, proteins, lipids, carbohydrates, minerals and vitamins can be efficiently used for vermicomposting nitrogen deficient organic wastes 18,19 . It is found abundantly in waste water ponds in the villages.…”
Section: Introductionmentioning
confidence: 99%